The Convergence of Science and Governance : Research, Health Policy, and American States - Fox, Daniel M. (Book collections on Project MUSE., 2010)
Daniel M. Fox gives an incisive assessment of the critical collaboration between researchers and public officials that has recently emerged to evaluate the effectiveness and comparative effectiveness of health services. Drawing on research as well as his first-hand experience in policymaking, Fox's broad-ranging analysis describes how politics, public finance and management, and advances in research methods made this convergence of science and governance possible. The book then widens into a sweeping history of central issues in research on health services and health governance during the past.